2012
DOI: 10.1007/s12094-012-0843-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study to compare oxaliplatin plus 5-fluorouracil and leucovorin (FOLFOX4) versus oxaliplatin plus raltitrexed (TOMOX) as first-line chemotherapy for advanced colorectal cancer

Abstract: IntroductionThe aim of this study was to compare TOMOX versus FOLFOX4 as first-line treatment of advanced colorectal cancer (CRC).Materials and methods191 chemotherapy-naïve patients were randomized to receive TOMOX or FOLFOX4. Patients were evaluated every 3 months and chemotherapy was continued until disease progression or unacceptable toxicity. Overall response rate was the primary endpoint.Results183 patients were included in the intent-to-treat analysis (92 TOMOX and 91 FOLFOX4). Overall response rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Martoni et al [11] Gravalos et al [5] Feliu et al Chiara et al [8] Cascinu et al [3] Carnaghi et al [ The referent regimens were FOLFIRI and FOLFOX in the study by Tournigand et al However, in both trials, a high proportion of patients switched to second-line irinotecan-based chemotherapy; this likely could have made the median OS longer compared with that observed in our series. In the trials included in our series, the rate of post-treatment therapies prescribed after raltitrexed failure reported by authors ranged from 50 to 60%, which was largely inferior to modern first-line trials where biological agents have been introduced.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Martoni et al [11] Gravalos et al [5] Feliu et al Chiara et al [8] Cascinu et al [3] Carnaghi et al [ The referent regimens were FOLFIRI and FOLFOX in the study by Tournigand et al However, in both trials, a high proportion of patients switched to second-line irinotecan-based chemotherapy; this likely could have made the median OS longer compared with that observed in our series. In the trials included in our series, the rate of post-treatment therapies prescribed after raltitrexed failure reported by authors ranged from 50 to 60%, which was largely inferior to modern first-line trials where biological agents have been introduced.…”
Section: Discussionmentioning
confidence: 62%
“…The results in the outcome of this pooled analysis appear similar even if slightly inferior to conventional FOLFOX and FOLFIRI regimens. In the headto-head comparison presented in the study by Gravalos et al [5], TOMOX was found to be noninferior to FOLFOX. In two randomized studies carried out by Goldberg and Tournigand, upfront FOLFOX4 was associated with RRs of 44 and 56%, a median PFS of 8 months, and a median OS of ∼ 20 months [16,17].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations